2021
DOI: 10.2196/31408
|View full text |Cite
|
Sign up to set email alerts
|

Technostress and Digital Competence Among Health Professionals in Swiss Psychiatric Hospitals: Cross-sectional Study

Abstract: Background Psychiatric hospitals are becoming increasingly digitized because of the disruptive rise in technical possibilities. This digitization leads to new tasks and demands for health professionals, which can have an impact on technostress. It is unclear whether digital competence reduces technostress and how technostress affects health professionals’ mental and physical health. Objective This study aims to assess the association between digital com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…Due to their recentness and thus lower prevalence in already published studies, these newly added factors are not primarily considered in this review. Instead, it focused on the most widely established five techno-stressors [ 10 , 106 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their recentness and thus lower prevalence in already published studies, these newly added factors are not primarily considered in this review. Instead, it focused on the most widely established five techno-stressors [ 10 , 106 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, from a transactional perspective, technostress is considered highly contextual [ 5 , 14 ]. Apart from situational specificity, individual perception and appraisal, it may also differ among occupational groups [ 134 ] or cultures [ 53 , 92 ]. The examination of different occupational groups, including diverse tasks and job demands, may therefore explain divergent results among the included studies [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another common source of technostress is caused by pressuring users to invest time and resources to learn and adopt them into their lives. A recent study in three Swiss psychiatric hospitals indicated that the introduction of digital technologies among healthcare professionals is causing them technostress ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…A better knowledge base, an ability to participate proactively in a change process, as well as a preparedness of physicians is associated with several positive outcomes for both physicians themselves and their patients [ 25 , 35 , 40 , 41 ]. For example, a higher knowledge base of physicians about digital technologies is associated with improved patient outcomes [ 35 ], higher quality of data resources [ 42 ], reduced stress in physicians [ 7 , 43 , 44 ], and higher workplace satisfaction [ 45 ]. High preparedness improves the adjustment to new situations and reduces procedure time, medical errors, and hospital costs [ 41 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%